Tolerability and effectiveness of povidone-iodine or mupirocin versus saline sinus irrigations for chronic rhinosinusitis - Lee, Victoria S. (Am J Otolaryngol, 2020)
OBJECTIVES: The role of topical anti-infectives in acute exacerbations of chronic rhinosinusitis is controversial. Povidone-iodine is an anti-bacterial and anti-viral that is affordable and available over-the-counter and may demonstrate advantages over mupirocin as a sinus irrigation therapy. The objective was to compare povidone-iodine or mupirocin versus saline sinus irrigations for sinusitis exacerbations in post-surgery subjects as well as to assess tolerability of povidone-iodine sinus irrigations. MATERIALS AND METHODS: This was a prospective single-blinded (clinician only) randomized controlled trial. Subjects were post-surgery with acute exacerbations of chronic rhinosinusitis and gram-positive bacteria on culture. They received povidone-iodine, mupirocin, or saline sinus irrigations, twice daily for 30 days. Outcomes were post-treatment culture negativity (primary) and Sinonasal Outcome Test-20 and Lund-Kennedy endoscopic score change (secondary). RESULTS: Of the 62 subjects analyzed, post-treatment culture negativity rate was higher in the MUP (14/20, 70%) group compared to the PI (9/21, 43%) and SAL (9/19, 47%) groups, although this was not significant (p=0.28). Povidone-iodine sinus irrigations at the 1% concentration were very well-tolerated, similar to saline irrigations. There were no significant differences in Sinonasal Outcome Test-20 score (povidone-iodine −0.3 [−0.6, 0.05] vs. mupirocin −0.3 [−0.7, 0.05] vs. saline −0.4 [−0.8, 0.05]; p=0.74) or Lund-Kennedy endoscopic score (povidone-iodine −3.5 [−7, −0.5] vs. mupirocin −2 [−4, 2] vs. saline −3 [−5, 0]; p=0.35) change. No serious adverse effects were reported. CONCLUSIONS: In patients who have had prior sinus surgery with acute exacerbations of CRS and gram-positive bacteria on culture, mupirocin sinus irrigations achieved a better post-treatment culture “control” rate compared to saline and povidone-iodine. In addition, 1% povidone-iodine solution was well-tolerated as a sinus irrigation and may represent a feasible method for temporarily disinfecting the sinonasal cavity of bacteria and viruses such as COVID-19.